Low-Grade Adenosquamous Carcinoma of the Axilla of Breast Origin in a Male: A Case Report and Literature Review - Yan, Xingqiang; Zhu, Fanshuang; Wang, Qiupeng; Chen, Lijie; Zhou, Yixing; Wu, Zenggui; Mei, Linhang; Ma, Zhaosheng; Cui, Binbin; Cao, Feilin (Frontiers in Oncology, 2020)
Low-grade adenosquamous carcinoma (LGASC) is a rare tumor occurring in the breast parenchyma. It is a rare type of low-grade invasive carcinoma of the breast, which was previously found only in females. In the case described herein, a 52-year-old male presented with a palpable mass lesion in his right axilla for 20 years; this is the first report of a male patient with LGASC. Pathology of core needle biopsy revealed a benign mass of mammary origin; however, the character of the mass was misdiagnosed. It was confirmed by postoperative pathology only after local excision, which indicated that the mass exhibited the typical pathological characteristics of LGASC. Immunohistochemically, we found positive expression of ER, which was inconsistent with the typical “triple-negative” immunophenotype of LGASC. Following resection of the mass, the patient was advised to regularly visit the clinic for follow-up, without the need for therapy because of the negative margins. In conclusion, LGASC should be considered in male patients with a mass lesion in their breast or axilla, even when core needle biopsy indicates a benign mass of breast origin. One-stage local resection is recommended for the treatment of male patients with LGASC; however, it is crucial to ensure that the margins are negative.